A law and finance theory of strategic blocking and preemptive bidding in takeovers - Högfeldt, Peter; Högholm, Kenneth (Journal of Corporate Finance, 2000)
This paper uses a law and finance approach to develop a new takeover theory that formalizes the idea that large target shareholders, who can block a takeover attempt, exercise a strategic influence on tender offer prices, and thereby, on the distribution of the takeover gain. The theory captures the interaction between legal rules, target ownership structure, bidder toehold and potential effects of arbitrageurs in an endogenously determined bargaining parameter that predicts a skewed distribution of the gain in favor of target shareholders. In a regression model, the parameter has significant explanatory power, specifically when the total takeover gain is positive.